2002
DOI: 10.1002/1521-396x(200208)192:2<301::aid-pssa301>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Laterally Coupled InGaN/GaN DFB Laser Diodes

Abstract: For group III nitride‐based lasers a new approach to realise DFB lasers and arrays is presented. Laterally coupled DFB (LC‐DFB) lasers are realised to minimise processing‐induced damage and to enable post‐processing adjustment of DFB laser parameters according to the material parameters achieved after epitaxial growth. These DFB laser arrays enable one to measure the threshold and the refractive index of electrically pumped DFB lasers over a wavelength emission range of 6 nm. DFB emission is demonstrated up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Surface gratings designs, all though simpler to fabricate, can compromise the quality of the p-type contact due to dry etch damage and are also prone to increased optical losses in the electrically un-pumped grating regions. Using shallow etched lateral grating designs, some of these issues are resolved [9], however deeply etched lateral gratings, [10], benefit from a much simpler fabrication route and have the potential for larger coupling coefficients. The authors have previously reported third order sidewall gratings in the InGaN/GaN material system [11][12], with single wavelength emission.…”
Section: Introductionmentioning
confidence: 99%
“…Surface gratings designs, all though simpler to fabricate, can compromise the quality of the p-type contact due to dry etch damage and are also prone to increased optical losses in the electrically un-pumped grating regions. Using shallow etched lateral grating designs, some of these issues are resolved [9], however deeply etched lateral gratings, [10], benefit from a much simpler fabrication route and have the potential for larger coupling coefficients. The authors have previously reported third order sidewall gratings in the InGaN/GaN material system [11][12], with single wavelength emission.…”
Section: Introductionmentioning
confidence: 99%
“…Both have their disadvantages, buried gratings require complex overgrowth steps which have the potential to introduce epi-defects and surface grating designs can compromise the quality of the ptype top contact [14] and suffer increased optical losses in electrically un-pumped grating regions. In our approach, gratings are formed along the sidewalls of a ridge waveguide laser diode [15] [16][17] [18]. It's one of the simplest ways to achieve single wavelength operation and has the advantage that the sidewall grating can be designed and implemented entirely post growth once the emission wavelength is known.…”
mentioning
confidence: 99%
“…In our approach, gratings are formed along the sidewalls of a ridge waveguide laser diode. [15][16][17][18] It is one of the simplest ways to achieve singlewavelength operation and has the advantage that the sidewall grating can be designed and implemented entirely postgrowth once the emission wavelength is known. Additionally, unlike surface and buried gratings, the coupling coefficient is determined mainly by the planar layout of the gratings rather than the etch depth, thereby increasing design freedom.…”
mentioning
confidence: 99%
“…GaN-based DFB LDs have been achieved by buried gratings [7,8,9], sidewall gratings, and surface gratings [10,11,12,13]. In the beginning, the first order DFB LD was achieved by establishing the buried gratings [14].…”
Section: Introductionmentioning
confidence: 99%